Psychological morbidity and chronic cough: which is predominant? A comparison of clinical characteristics - Tongyangzi Zhang; Heng Wu; Wanzhen Li; Xing Cui; Yiqing Zhu; Shengyuan Wang; Wenbo Shi; Siwan Wen; Cuiqin Shi; Xianghuai Xu; Li Yu (SAGE Publishing, 2023)
Background: The clinical characteristics of chronic cough with pre-existing psychological co-morbidity (PCC) and chronic cough with secondary anxiety and depression (SCC) were compared to provide a basis for diagnosing and treating psychological co-morbidities in people with chronic cough. Methods: A prospective study was conducted to analyze the general clinical data between the PCC, SCC, and the chronic cough without anxiety and depression (CC) groups. A total of 203 patients with chronic cough were enrolled in the study. The final diagnosis was made in all cases using a combination of psychosomatic and respiratory diagnoses. The three groups' general clinical data, capsaicin cough sensitivity, cough symptom score, Leicester cough questionnaire (LCQ), and psychosomatic scale scores were compared among the three groups. The diagnostic value of the patient health questionnaire (PHQ)-9 and general anxiety disorder (GAD)-7 in patients with PCC and the follow-up information were analyzed. Results: Compared with the SCC group, the duration of cough in the PCC group was shorter (H = −3.54, p  = 0.001), the night cough symptoms were milder (H = −4.60, p  < 0.001), the total LCQ score was lower (H = −2.97, p  = 0.009), and the PHQ-9 (H = 2.90, p  = 0.011) and GAD-7 scores (H = 2.71, p  = 0.002) were higher. When using PHQ-9 and GAD-7 scores for the combined prediction and diagnosis of PCC, the area under the curve (AUC) was 0.88, and the sensitivity and specificity were 90.0% and 73.85%, respectively. After 8 weeks of psychosomatic treatment, cough symptoms improved in the PCC group, but the psychological improvement was not significant. The psychological status of the SCC group improved after cough symptoms were ameliorated by etiologic or empirical treatment. Conclusion: The clinical characteristics of patients with PCC and SCC are different. The evaluation of psychosomatic scales is of value to distinguish between the two groups. Chronic cough patients with psychological co-morbidity benefit from the combined diagnosis of psychosomatic medicine in a timely fashion. PCC requires more attention in psychological therapy, but for SCC, targeting etiological treatment of the cough is preferred. Trial registration: The protocol was registered in the Chinese Clinical Trials Register ( http://www.chictr.org.cn/ ) [ChiCTR2000037429].